2019
DOI: 10.1080/00071005.2019.1581128
|View full text |Cite
|
Sign up to set email alerts
|

Adding Lemon Juice to Poison – Raising Critical Questions About the Oxymoronic Nature of Mindfulness in Education and Its Future Direction

Abstract: This article seeks to amplify a debate initiated in this journal by Hyland (2016) by deepening a number of conceptual, methodological and implementational issues concerning the application of mindfulness based interventions (MBIs) to schools and other places of learning. It argues that the pursuit of the byproducts of mindfulness, enhanced focus and well-being, serve a neoliberal agenda for education. This is lemon-juice to poison as it encourages students to accept and cope with oppressive structures partiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 30 publications
2
52
0
3
Order By: Relevance
“…It was observed that the key element that links the different elements taught during the workshop (both in content and form) is the figure of the instructor. The relevance of the instructor's personal mindfulness practice has always been one of the focuses of interventions based on mindfulness [44,60], as the cultivation of a mindful teacher presence within the educational setting represents a permanent necessity and challenge [61,62] in order to offer concrete examples of what is being taught during the workshop [63]. The teacher's self-disclosure appears to generate greater trust and a more horizontal relationship with the participants, who can explicitly and implicitly recognize the teacher's humanity, rather than a vertical relationship in which the teacher is perceived as a figure of complete authority.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the key element that links the different elements taught during the workshop (both in content and form) is the figure of the instructor. The relevance of the instructor's personal mindfulness practice has always been one of the focuses of interventions based on mindfulness [44,60], as the cultivation of a mindful teacher presence within the educational setting represents a permanent necessity and challenge [61,62] in order to offer concrete examples of what is being taught during the workshop [63]. The teacher's self-disclosure appears to generate greater trust and a more horizontal relationship with the participants, who can explicitly and implicitly recognize the teacher's humanity, rather than a vertical relationship in which the teacher is perceived as a figure of complete authority.…”
Section: Discussionmentioning
confidence: 99%
“…This is contrasted with mindfulness 'as' education, which emphasises a more holistic approach, where mindfulness, understood as deepened awareness permeates all aspects of the system, including relationships, curriculum and pedagogy. A similar categorization has been employed by Ergas (2019b), who adds mindfulness 'of' to 'in' and 'as' education. This third category, also discussed by Sellman & Buttarazzi (2020), but subsumed by mindfulness 'as' education, engages a more critical form of mindfulness to include understanding the nature of education and the education system, including its more covert functions such as conditioning and reproduction of wealth. In Ergas and Linor (2019) and Ergas (2019a), it's clear that mindfulness 'as' education is rare, and mindfulness 'of' education is rarer still, some university courses with social justice outlooks excepted (e.g.…”
Section: Modalities Of Mindfulness Within Educationmentioning
confidence: 99%
“…Forbes 2019, Hyland 2016, Kristensen 2018, Ng 2016, Purser 2019, Reveley 2016, Walsh 2016, van Dam et al 2018 to analyse and group these effects. After introducing different modalities of mindfulness within education that aid our classification (Ergas 2019a, Sellman & Buttarazzi, 2020, we initially focus our critique on the most common, instrumental applications. We posit that the main effect of mindfulness is enhanced awareness, which can result in two classifications: positive and negative 'side-effects', when understood from a simplicity paradigm of linear and temporal causality, though positive side-effects are more frequently reported.…”
Section: Introductionmentioning
confidence: 99%
“…This would benefit both students' mental health and their academic success. Ergas (2015) pointed out to what extent promoting mindful attention in students has the potential to reconstruct education and foster development of the "whole person" (for a critical review of mindfulness in education see Sellman and Buttarazzi, 2019): since mindfulness is a purposeful way of attending, it is subject to an intentional choice of the individual regarding the object that they want to focus their attention on. Hence, mindfulness can (re-)establish the value of a firstperson perspective in addition to the third-person perspective predominant in current educational systems.…”
Section: Introductionmentioning
confidence: 99%